Analisis Dan Perancangan Pada Aplikasi Absensi Siswa Cakra Index - Alfathir Rizky Harsya; Faiz Naufal Putra Permana (Journal of Information Systems and Business Technology, 2025)
The rapid growth of information technology has brought major changes in various aspects of life, including office and school administration. This paper aims to design and develop an integrated, accurate, and effective student attendance recording system. The stages of the waterfall method applied in both development and design are needs analysis, system design, implementation, and testing. The Laravel framework and Mysql database are used to build this system. Black box testing aims to verify that the website is running as expected. The test results show that the website is running well with all specified requirements met. UAT helps evaluate the system to meet end user needs. Therefore, this system will function as an efficient digital tool for recording student attendance.